Análise do conceito conforto na enfermagem a partir do método evolucionário - Vale, Sara Cordeiro Eloia (2023)
Comfort is a concept related to the origin and development of nursing. It presents varied interpretations and continues without a consensus. In this context, the present study aims to: analyze the concept of comfort in the nursing discipline, its constituent components and related elements, according to Rodgers' evolutionary method; compare the attributes, antecedents and consequences of this concept with the elements of the nursing diagnosis Impaired comfort; and review the structural elements of this diagnosis (label, related factor and defining characteristic). The evolutionary method of concept analysis according to Rodgers was used, operationalized by the scope review. Eight methodological phases were reported to contemplate the execution of these methods, respecting all the determinations of the theorists. The databases used were: Medline/PubMed (via National Library of Medicine), Cinahl, Scopus, Web of Science and Lilacs. Inclusion criteria were studies available electronically in full text and that presented comfort in the nursing work process. There was no delimitation of languages and period of publication. Those who did not respond to at least one of the research questions and who involved the concept of comfort only as part of the theoretical framework were excluded. Abstracts published in annals of events, dissertations, theses and letters to the editor were also defined as exclusion criteria. The search strategy occurred through the first two recommended steps. The third was not necessary due to the scope of the adequate sample. In order to ensure rigor in conducting the review, the PRISMA Extension for Scoping Reviews (PRISMA-ScR) flowchart was used and data extraction was performed using a form adapted according to JBI recommendations. The analysis process was also carried out according to the theorists. Comfort was analyzed in different contexts of clinical practice and training, applied in different situations with different populations. It presented interdependent attributes. In an attempt to define it, it is exposed: the complex and subjective characteristics were related to different contextual variations of comfort. The holistic, individualized and dynamic attributes influenced the assessment of the individual's basic needs and comfort needs arising from uncomfortable situations. The care process was related to the ways and means of comforting with the promotion of well-being based on social and situational interactions. Comfort was presented as a positive result that meant the satisfaction of multidimensional needs, the absence of unpleasant sensations, the restoration of health. As for antecedents, emphasis was given to uncomfortable events/situations and the subjects' responses to discomfort. The concept was also preceded by care measures and behaviors of the subjects in the search for comfort, which meant that prior discomfort was not necessary. The analysis of the consequences was considered challenging due to their specific description. Two main consequences were highlighted: patient, family and team satisfaction, and feeling at ease. It is hoped that the results of this investigation will form a basis for continued research into comfort.